IPY PPS Arctic Canada: Impacts of a Changing Treeline - Photos and Plants Through Time - Karen Harper; Nancy C. Doubleday (Polar Data Catalogue, 2012)
This research project used qualitative methods: 1) photography and photo interpretation, 2) community mapping of landscape, land-use and vegetation, and 3) bringing together (synthesis) of observed environmental, social, and cultural changes and their relation to health and well being connected to the changes shown in the photographs, collections, and community mapping. The results were shared first with community partners, then disseminated more widely via IPY websites under the IPY data management and storage protocols. The conditions of the Informed Consent agreements and the Releases for Intellectual Property, for photographing individuals and for use of existing photographs, were strictly adhered to. We expect to publish in popular and scientific literature and also to contribute with our PPS project partners (Harper and Ross at Dalhousie, et al.) to the development of materials for school curriculum modules. Full credit will be given to work by community partners in all research contributions and publications, unless individuals have specifically requested confidentiality or anonymity. Results will be shared through the IPY Canada Office, the PPS Arctic Website, the Nunavut Research Institute, and local organizations, as well as mailed or emailed to participants.